Beyond Traditional Techniques for Enhancement of Digital Forensics for Cloud - Khawaja Qasim Maqbool,; Osama Farooq,; Muhammad Zunnurain Hussain,; Muhammad Zulkifl Hasan,; Hiba Batool,; Fatima Usman, (Spectrum of Engineering Sciences, 2024)
In the recent years, cloud computing has stepped into the shoes of the conventional IT, featuring scalability, flexibility, and cost-effectiveness among others. Despite the distributed nature of cloud infrastructure and the dynamic allocation of virtual resources though, these present unique challenges to the investigators looking to collect and preserve the evidence. The following article deals with the gaps and difficulties in cloud forensics by creating a solution through effective digital forensic while integrating robust chain of custody procedures. The proposed solution combines a broad literature review, the examination of actual cloud data, and the developing of unique forensic techniques particularly suitable for cloud networks. This research utilizes various methods which include implements of dynamic evidence collection, cloud-specific artifact analysis, and machine learning techniques that are designed to enhance cloud forensic investigations with regard to effectiveness and efficiency. Besides that, the article illustrates the key facet of standardized frameworks and applying legal and regulatory requirements for digital evidence admissibility in the court. Such a collaboration can be achieved through joint research projects, knowledge sharing, and making progress in forensic methods consistently, so that the cloud will be less susceptible to security breaches. Keywords: Cloud Forensics; Evidence Analysis; Forensics, Tool; Cloud Computing